Oxygen depletion recorded in upper waters of the glacial Southern Ocean - Zunli Lu; Babette A. A. Hoogakker; Claus-Dieter Hillenbrand; Xiaoli Zhou; Ellen Thomas; Kristina M. Gutchess; Wanyi Lu; Luke Jones; Rosalind E. M. Rickaby (Nature Communications, 2016)
Oxygen depletion in the ocean interior may be closely linked to atmospheric CO2level, yet robust proxies are scarce. Here, using foraminiferal I/Ca as a proxy for oxygenation changes, the authors show that oxygen depletion in the upper waters of the high latitude Southern Ocean occurred during glacials.